2006
DOI: 10.1186/1743-422x-3-41
|View full text |Cite
|
Sign up to set email alerts
|

The role of single N-glycans in proteolytic processing and cell surface transport of the Lassa virus glycoprotein GP-C

Abstract: Lassa virus glycoprotein is synthesised as a precursor (preGP-C) into the lumen of the endoplasmic reticulum. After cotranslational cleavage of the signal peptide, the immature GP-C is posttranslationally processed into the N-terminal subunit GP-1 and the C-terminal subunit GP-2 by the host cell subtilase SKI-1/S1P. The glycoprotein precursor contains eleven potential Nglycosylation sites. In this report, we investigated the effect of each N-glycan on proteolytic cleavage and cell surface transport by disrupti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 27 publications
1
57
0
3
Order By: Relevance
“…Arenavirus GP N-linked glycans play significant biochemical roles in virus-cell interactions (34,35). Previous studies found that specific N-linked glycans in LCMV GP1 were necessary for GP trafficking, fusion activity, and infectivity (34).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Arenavirus GP N-linked glycans play significant biochemical roles in virus-cell interactions (34,35). Previous studies found that specific N-linked glycans in LCMV GP1 were necessary for GP trafficking, fusion activity, and infectivity (34).…”
Section: Resultsmentioning
confidence: 99%
“…LASV GP1 contains seven conserved N-linked glycosylation sites. Removing glycans at positions 81, 91, 101, and 121 was previously shown to inhibit GPC processing into GP1 and GP2 (35), although receptor binding and fusion activity were not evaluated. We reproduced the seven N-glycan mutants by changing glycosylation site motifs from N-X-S/T to N-X-A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LASV GPC contains eleven potential N-glycosylation sites, but disruption of only six of them affected GPC processing indicating that these N-glycans were essential for correct conformation of GPC in order to be cleaved by the host cell subtilase [168]. The LCMV GPC contains eight potentially glycosylated sites [169].…”
Section: The Lassa Virus Signal Peptide and Gpc Processingmentioning
confidence: 99%
“…гликопротеины G1 и G2 содержат несколько участков гликозилирования, которые являются необ-ходимыми для осуществления белками своих функ-ций [18]. в частности, гликопротеин вируса ласса содержит шесть участков гликозилирования [5].…”
unclassified